Discovery of non-proteinogenic amino acids inhibiting biofilm formation by S. aureus and methicillin-resistant S. aureus. (15th September 2021) - Ikeda, Kentaro; Shoda, Takuji; Demizu, Yosuke; Tsuji, Genichiro
Graphical abstract: Abstract: Bacterial biofilms often cause medical complications and there has been a great deal of interest in the discovery of small-molecule agents that can inhibit the formation of biofilms. Among these agents, it has been reported that several d -amino acids, such as d -Leu, d -Trp, d -Tyr, and d -Met, exhibit weak inhibitory activity toward bacterial biofilm formation. In this study, we have screened a library of 332 non-proteinogenic amino acids for new biofilm inhibitory agents and discovered several compounds exhibiting biofilm-inhibitory activity against Gram-positive bacteria. In particular, H-DL-β-(3, 4-dihydroxyphenyl)-dl -Ser-OH (253 ) showed potent activity against S . aureus, including methicillin-resistant S. aureus .